The Differences of Folliculogenesis between Treated with Letrozole and Letrozole-Electroacupuncture in Women with Polycystic Ovary Syndrome - Yulyanti, Yulyanti; Budihastuti, Uki Retno; Melinawati, Eriana; Sulistyowati, Sri; Nurwati, Ida (Indonesian Journal of Medicine, 2020)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that most often causes infertility. It occurs due to the failure of folliculogenesis, thus causing non-ovulation. Letrozole is a 3rd generation drug of non-steroidal aromatase inhibitors, which can increase ovulation rates. Electroacupuncture is the insertion and manipulation of needles into acupuncture points (acupoints) that are selected specifically based on the meridian system and connected to the electrode stimulator. This study aimed to determine the differences of the effects of letrozole and letrozoleelectroacupuncture (letrozole-EA) on the improvement of folliculogenesis in women with PCOS.Subjects and Method: This was an analytic observational study with a case-control design. This study was conducted at the Gynecology Polyclinic and Sekar Clinic, Dr. Moewardi Hospital, Surakarta. A sample of 30 infertile women aged 20-45 years was selected by fixed disease sampling. The criteria of the PCOS were determined based on Rotterdam criteria. The dependent variable was the diameter of the follicle. The independent variables were the administration of letrozole and letrozole-EA. Transvaginal ultrasound of Voluson P6 was used to measure the folliculogenesis. The data were analyzed by independent t-test.Results: On the second day after treatment, the diameter of the follicles in the letrozole-EA group (mean= 6.92; SD= 1.60) was bigger than the letrozole group (mean=5.66; SD=1.11), and it was statistically significant (p=0.004).Conclusion: Combination of letrozole and letrozole-EA therapy is more effective in increasing follicular diameter development than letrozole therapy only.Keywords: polycystic ovary syndrome, folliculogenesis, Letrozole, electro-acupunctureCorrespondence: Yulyanti. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia. Email: dr.yulyanti@gmail.com. Seluler: +6285264806570.Indonesian Journal of Medicine (2020), 05(03): 214-223https://doi.org/10.26911/theijmed.2020.05.03.06